Registration in the commercial register as a means of giving publicity to the free management contract of a commercial business - Wahiba, Adryen Chiraz (The International tax journal, 2026)
This study aims to highlight the fundamental role of registration in the Commercial Register as a legal mechanism for ensuring publicity and transparency in the lease-management contract of a commercial business under Algerian legislation. It does so by analyzing the legal framework governing the Commercial Register, particularly the provisions of Law No. 04-08 and Executive Decree No. 15-111. The study also seeks to clarify how registration enables the determination of the true legal status of the operator of the commercial business, distinguishing between the capacity of the owner and that of the tenant-manager, thereby ensuring the provision of information to third parties and the protection of contracting parties and creditors. Registration in the Commercial Register is not merely a formal administrative procedure; rather, it constitutes a legal instrument with constitutive effect, especially for the tenant-manager who acquires the status of a trader upon registration. Furthermore, legal publicity contributes to achieving legal certainty and the stability of commercial transactions. However, its effectiveness remains limited due to the absence of strict legal provisions specifying sanctions for non-compliance with registration and amendment procedures, which calls for strengthening the relevant legislative framework.